PELATIHAN KETERAMPILAN PEMBUATAN KUPINGU (KUE PIA UBI UNGU) PADA IBU-IBU RUMAH TANGGA DI GAMPONG GUGOP PULO ACEH KABUPATEN ACEH BESAR (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Gampong Gugop is a village which is located in the structure of Pulo Aceh (Pulo Breuh). The village is surrounded by the ocean. The majority of the livelihoods of the surrounding community are fishermen, and most of the residents have a very low level of education. Therefore, the Community Partnership Program (PKM) activities broadly aim to provide food skills training to community members, especially housewives. The priority problem for partners is the number of housewives who are less productive which causes low income per capita . PKM offers a solution to overcome this problem. The solution is to provide skills training in the food sector. Especially the skill of making Kupingu (purple sweet potato pie) with the demonstration method. The results achieved after the training, (a) partners become motivated and enthusiasm in building the family economy. (b) procurement of equipment to support the Kupingu production process (c) training on good and neat product packaging, finance, marketing and product innovation training. This activity is expected to provide benefits and facilitate the development of partner businesses and provide a multiplier effect on other types of food businesses.